Successful pregnancy with epidermal growth factor receptor tyrosine kinase inhibitor treatment of metastatic lung adenocarcinoma presenting with respiratory failure - Lee, C.H.; Liam, C.K.; Pang, Y.K.; Chua, K.T.; Lim, B.K.; Lai, N.L. (2011)
We report a woman presenting with respiratory failure due to a right-sided pleural effusion, lung metastases and lymphangitis carcinomatosis from advanced lung adenocarcinoma in the third trimester of pregnancy, who showed good response to EGFR tyrosine kinase inhibitor.